Components in graphs of diagram groups over the union of two semigroup presentations of integers(Kumpulan-kumpulan gambar rajah atas kesatuan dua persembahan semikumpulan bagi integer) - Gheisari, Yousof; Abd. Ghafur Ahmad (Universiti Kebangsaan Malaysia, 2012)
Given any semigroup presentation, we may obtain the diagram group. The purpose of this paper is to determine the graphs Γn(P), (n ∈ N), which are obtained from diagram group for the union of two semigroup presentation of integers with s and t different initial generators. The number of vertices and edges in these graphs will be computed.